Unions, work-related training, and wages : evidence for British men - Booth, Alison L. [Verfasser]; Francesconi, Marco [Verfasser]; Zoega, Gylfi [Verfasser] (My University, 2003)
"Using data for the years 1991-96 from the British Household Panel Survey, the authors investigate how union coverage affected work- related training and how the union-training link affected wages and wage growth for a sample of full-time men. Relative to non-covered workers, union-covered workers were more likely to receive training and also received more days of training. Among workers who received training, those with union coverage enjoyed greater returns to training and higher wage growth than did those without. While some of these results have been found in previous studies, others are new. The wage results, in particular, suggest a need for rethinking the conventional view that union wage formation in Britain reduces the incentives to acquire work-related training." (author's abstract, IAB-Doku) ((en))
Keywords: S 5.3 Personalentwicklung; G 1.3.1.2 Weiterbildungsmarkt; G 1.2.2.1 Lohn- & Tarifsysteme; I 2.2.1 Westeuropa; Männer; Betriebliche Weiterbildung; Erfolgskontrolle; Bildungsertrag; Lohnhöhe; Quantitative Angaben; Großbritannien; 1991-1996